MODERATION IN ISLAMIC EDUCATION IN LIGHT OF THE PROPHET’S HADITH - Arsyad, Yusri Muhammad; Subaedah, S.; Bazit, Ahmad; Anwar, Yunus; Abdul Karim, Bishri (Jurnal 'Ulwan, 2025)
Islam is a moderate religion, and its moderation is proven by examining its beliefs, principles, scientific foundations, morals, worship, laws, and rulings represented in an educational process in all aspects of social life through the Prophetic Hadith. Moderation and moderation of the educational process consisting of the following three main elements: Moderation of educational belief; Moderation of worship and rituals; Moderation of morals in the educational process: One of the applications of the educational process in Islam is its moderation and moderation in morals; how to deal with morals and modify their concept among people; For example, the morality of justice, which Islam calls for, includes giving all those who have rights their rights. The morality of patience in Islam comes in the middle between indifference and negligence, and between quick anger and lack of self-control. The morality of generosity comes between extravagance and waste, and between withholding and miserliness. The morality of tolerance comes between the extremes of losing rights and oppressing oneself and allowing others to attack it, and between oppression, transgression and injustice.